(untitled) (Agriculture, Food, and Natural Resources Journal, 2026)
Productivity of maize in sub-Saharan Africa is declining due to poor soil health and fertility, low seed yield, and biotic and abiotic stresses. Baby trials were established on farms in humid agro-ecology during 2020-2021. Morpho-physiological, fodder and seed yield differences among maize genotypes grown on farmers’ fields and preferences for traits across years were investigated. A completely randomized design with each farmer’s location as a replicate was used. The weather attributes, soil physical and chemical properties, agronomic, fodder and seed yield were measured. The analysis of variance for 2020 and 2021 data was performed using PROC GLM procedure of Statistical Analysis System (Version 9.0). Farmers’ assessment was used to identify preferences for traits and challenges to production. Findings showed high variability for earliness, fodder and seed yield traits. Ear length and width, kernel row-1 were responsive to environmental factors over the years. The year effect was important in defining earliness, seed yield and yield traits. Across years ’DMR-ESR-Y’ was earlier with short anther-silk-interval. ‘DMR-LSR-Y’ performed best for seed yield compared to ‘Oba super 6’ and ‘LNTP-SR-Y’. ‘Oba super 2’ gave the highest mean value for stover dry yield. Baby trials at Ado-Odo, Isaboro and Ayetoro villages had the highest seed yield. The stover dry weight peaked in Ayetoro. Findings support the development of extra early and early maturing varieties. ‘DMR-ESR-Y’, ‘DMR-LSR-Y’ and ‘LNTP-SR-Y’ are recommended for short cycle production, and as donor parents for fodder, seed yield, and total dry yield.